PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE QUIZ TEAM TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII.2 MTsN DURIAN TARUNG PADANG - Nolisa, Eva; Rismen, Sefna; Mardiyah, Ainil (Pendidikan Matematika, 2014)
ABSTRACTThe background from this research is a low comprehension studentsâ mathematics concept at MTsN Durian Tarung Padang. The aim from this research is to know the comprehension studentsâ mathematics which use active learning strategies Quiz team more better from a comprehension studentsâ with use a conventional learning. A kind from this research is experiment with purposive sampling. The instrument is a comprehension studentsâ mathematics test like essay with reliability test is Â = 0,86. Analysis data technique which use is t-test in one side with Minitab. According to the hypothesis testing results obtained tvalue=3,33Â  is greater than ttable=1,66 so that the hypothesis research is accepted. It can be concluded that the students comprehension of mathematical concepts by applying active learning strategies Quiz team with better than students in the class VIII.2 comprehension of mathematical concepts with conventional learning students in the class VIII.3 at the level of 95% in MTsN Durian tarung Padang.